PENGARUH ONLINE CUSTOMER REVIEW, ONLINE CUSTOMER RATING, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK MAKE OVER PADA TIKTOK SHOP - Putu Pade Sintia Damayanti; Ni Putu Cempaka Dharmadewi Atmaja; Daniel Manek (EMAS, 2023)
The use of the internet is not limited to accessing information on one medium, but can also be used as a means to make buying and selling transactions, making it easier to develop a broad business network without being limited by distance and time. This study aims to explain the influence of online customer reviews, online customer ratings, and price perceptions on purchasing decisions for Make Over products at the TikTok Shop. The research population is consumers who have shopped for Make Over products at the TikTok Shop and live in the Denpasar area. The sample in this study was 100 respondents, which were determined based on purposive sampling and accidental sampling methods. The analytical tool used to test the hypothesis is multiple linear regression. The results of the study show that online customer reviews and online customer ratings have a positive and significant effect on purchasing decisions. the price perception variable has no significant positive effect on purchasing decisions.